Sodium battery positive electrode material and preparation method and application thereof

By adopting NaaNibTicFedMneXfO2 chemical formula sodium electropositive electrode material, combined with surface coating of Cu or Ag elements and double sintering treatment, the problem of structural stability of existing materials when improving Fe element content is solved, and high energy density, conductivity and cyclic stability are achieved.

CN119764437AActive Publication Date: 2025-04-04NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411891218.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-04
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

At this stage, sodium electropositive cathode materials have defects that cannot be taken into account both energy density, conductivity and cycle stability, and it is difficult to maintain structural stability while increasing the Fe element content.

Method used

NaaNibTicFedMneXfO2 is used as the chemical formula of sodium electropositive electrode material, where X element is Cu or Ag, and the proportion of X element on the surface mass of the material is 0.5 wt%-2 wt%. The material is prepared by two sintering treatments. The first sintering temperature is 850-1000°C and the second sintering temperature is 400-800°C to stabilize the structure and improve the conductivity.

Benefits of technology

The first discharge capacity, conductivity and cycle stability of sodium-electrode material are achieved, which are characterized by the first discharge capacity greater than or equal to 130mAh/g, the powder resistance is less than or equal to 320,000Ω*cm under 18MPa pressure, the capacity retention rate after 100 cycles is greater than or equal to 94.5%, and the dissolution amount of Fe element of the negative electrode is less than or equal to 50ppm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764437A_ABST
    Figure CN119764437A_ABST
Patent Text Reader

Abstract

The invention provides a sodium battery positive electrode material and a preparation method and application thereof, the general formula of the sodium battery positive electrode material is NaaNibTicFedMneXfO2, a is greater than or equal to 0.94 and less than or equal to 1.04, b is greater than or equal to 0.20 and less than or equal to 0.30, c is greater than or equal to 0.03 and less than or equal to 0.1, d is greater than or equal to 0.3 and less than or equal to 0.4, e is greater than or equal to 0.3 and less than or equal to 0.5, f is greater than or equal to 0.001 and less than or equal to 0.02, and an X element is selected from at least one of Cu and Ag; the ratio of the element X on the surface of the sodium battery positive electrode material is 0.5 wt%-2wt%. The sodium battery positive electrode material provided by the invention has the characteristics of relatively high first discharge capacity, conductivity and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a sodium positive electrode material, in particular to a sodium positive electrode material and a preparation method and application thereof, belonging to the field of new energy. Background Art

[0002] At present, the valence of Fe in sodium battery layered cathode materials is above 3V, so introducing more Fe can increase the average voltage of the battery cell while reducing costs. However, the valence of Fe will lead to the Jan-Taylor effect, causing major changes in the structure. Therefore, it is particularly important to stabilize the structure while increasing the Fe content.

[0003] Chinese patent CN117800411A provides a sodium positive electrode material precursor uniformly doped with stable valence elements and its preparation method, and sodium positive electrode material. The patent stabilizes the metal oxygen bond and expands the unit cell volume by doping elements, and the sodium positive electrode material prepared by the precursor has a more stable structure, better capacity and cycle performance. The patent discloses a technical solution that focuses on precursor improvement by doping elements to stabilize metal oxygen bonds and expand unit cell volume, but has the defects of low efficiency and limited capacity improvement.

[0004] Chinese patent CN117712349A discloses coating materials for positive electrode materials of sodium ion batteries, positive electrode materials for sodium ion batteries and preparation methods, sodium ion batteries, and electrical equipment. The coating materials provided by the patent are slightly soluble in water, have high air stability, and high ion conductivity. When used as coating materials for positive electrode materials of sodium ion batteries, the storage performance, interface stability, and sodium ion diffusion capacity of the resulting positive electrode materials can be effectively improved. It can also effectively reduce the contact area between the positive electrode material and the electrolyte during the cycle, alleviate the side reactions between the electrode materials, and thus improve the electrochemical performance of the battery. However, since the patent uses a Bi coating method to improve the surface, the Bi conductivity is low, and the process is three sinterings, and the phosphate coating stability is poor, so there are defects in poor conductivity and cycle stability.

[0005] From the above content, it can be seen that at the current stage, sodium battery positive electrode materials have the defects of energy density, conductivity and cycle stability that cannot be taken into account at the same time.

[0006] Therefore, developing a sodium battery positive electrode material with high first discharge capacity, conductivity and cycle stability has become a research direction in this field. Summary of the invention

[0007] The invention provides a sodium battery positive electrode material, which has the characteristics of high initial discharge capacity, high conductivity and high cycle stability.

[0008] The invention also provides a method for preparing a sodium positive electrode material, which has the characteristic of simple operation.

[0009] The present invention also provides a positive electrode sheet, which has the characteristics of high initial discharge capacity, conductivity and cycle stability.

[0010] The invention also provides a battery, which has the characteristics of high initial discharge capacity, high conductivity and high cycle stability.

[0011] The present invention provides a sodium positive electrode material, wherein the general formula of the sodium positive electrode material is Na a Ni b Ti c Fe d Mn e X f O2, wherein: 0.94≤a≤1.04, 0.20≤b≤0.30, 0.001≤c≤0.1, 0.3≤d≤0.4, 0.3≤e≤0.5, 0.001≤f≤0.02, X element is selected from at least one of Cu and Ag; the X element accounts for 0.5wt%-2wt% of the surface mass of the sodium positive electrode material.

[0012] The sodium-based positive electrode material as described above, wherein the first discharge capacity of the sodium-based positive electrode material is greater than or equal to 130 mAh / g; and / or,

[0013] The powder resistance under a pressure of 18 MPa is less than or equal to 320,000 Ω*cm; and / or,

[0014] After the full battery including the positive electrode material is cycled 100 times in a 45°C environment, the capacity retention rate is greater than or equal to 94.5%, and the Fe element dissolution amount of the negative electrode is less than or equal to 50 ppm.

[0015] The sodium-based positive electrode material as described above, wherein the single-particle compressive strength of the sodium-based positive electrode material is greater than or equal to 190 MPa; and / or,

[0016] The Dv3 of the sodium positive electrode material is greater than 2 μm;

[0017] In the dQ / dV spectrum of a full battery including the positive electrode material measured after 100 cycles in a 45°C environment, no irreversible phase change occurs in the 3.7-4V range; and / or,

[0018] The average voltage of the button cell 2-4V including the positive electrode material is greater than or equal to 3.1V.

[0019] The present invention also provides a method for preparing a sodium positive electrode material, which comprises the following steps:

[0020] 1) performing a first sintering treatment on a mixed system including a nickel iron manganese oxide precursor, a titanium source and a sodium source to obtain a first sintered product;

[0021] 2) performing a second sintering treatment on the mixed system including the first sintered product and the X element metal source to obtain the sodium battery positive electrode material;

[0022] The treatment temperature of the first sintering treatment is 850-1000°C, and the holding time is 8-14h;

[0023] The treatment temperature of the second sintering treatment is 400-800°C, and the holding time is 6-12h;

[0024] The general formula of the nickel iron manganese oxide precursor is Ni b Fe d Mn e (OH)2, 0.20≤b≤0.30, 0.3≤d≤0.4, 0.3≤e≤0.5.

[0025] The method for preparing the sodium positive electrode material as described above, wherein the first sintering treatment comprises first heating the temperature to 600-700°C at a heating rate of 4-8°C / min, then heating the temperature to 850-1000°C at a heating rate of 1-2°C / min, and keeping the temperature for 8-14h; and / or,

[0026] The second sintering treatment includes heating the temperature to 400-800° C. at a heating rate of 1-5° C. / min and keeping the temperature for 6-12 hours.

[0027] In the method for preparing the sodium positive electrode material as described above, the X element includes copper and silver, and the molar ratio of copper to silver is 1:(0.6-1.5).

[0028] The method for preparing the sodium positive electrode material as described above further comprises cooling the product obtained by the first sintering treatment to room temperature at a rate of 2-5°C / min.

[0029] In the method for preparing the sodium positive electrode material as described above, the X element metal source is selected from at least one of copper oxide and silver oxide.

[0030] The present invention also provides a positive electrode sheet, which comprises any one of the above-mentioned sodium battery positive electrode materials.

[0031] The present invention also provides a battery, which comprises any one of the above-mentioned sodium positive electrode materials; and /

[0032] or,

[0033] Including any of the above positive electrode sheets.

[0034] The sodium battery positive electrode material provided by the present invention has the characteristics of high energy density, electrical conductivity and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a SEM image of the sodium positive electrode material prepared in Example 1;

[0036] Figure 2 This is a SEM image of the sodium positive electrode material prepared in Example 2;

[0037] Figure 3 This is a SEM image of the sodium positive electrode material prepared in Comparative Example 1;

[0038] Figure 4 This is the XRD pattern of the sodium positive electrode material prepared in Example 1;

[0039] Figure 5 Schematic diagram of the cross-section SEM sampling point positions of the sodium positive electrode material prepared in Example 1;

[0040] Figure 6 The silver element content distribution data of each sampling point of the sodium battery positive electrode material prepared in Example 1. DETAILED DESCRIPTION

[0041] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0042] The first aspect of the present invention provides a sodium positive electrode material, the general formula of which is Na a Ni b Ti c Fe d Mn e X f O2, wherein: 0.94≤a≤1.04, 0.20≤b≤0.30, 0.03≤c≤0.1, 0.3≤d≤0.4, 0.3≤e≤0.5, 0.001≤f≤0.02, X is selected from at least one of Cu and Ag; the surface mass proportion of X element in the sodium positive electrode material is 0.5wt%-2wt%.

[0043] The inventors have found that the sodium positive electrode material provided by the present invention has the characteristics of high initial discharge capacity, conductivity and cycle stability. Based on the above phenomenon, the inventors speculate that the reason may be:

[0044] First, the positive electrode material has a suitable iron content and titanium content, wherein Fe can participate in the valence change during the charge and discharge process, provide capacity and high average voltage, and make the sodium positive electrode material have a higher energy density. However, high Fe is easy to cause structural instability, so titanium is introduced. Titanium can stabilize the structure of the sodium positive electrode material by forming the second phase particles through solid solution, so that the sodium positive electrode material has a higher energy density and cycle stability. Secondly, the surface of the positive electrode material is coated with the stabilizing element Ti, which can further improve the cycle stability of the sodium positive electrode material. Thirdly, the Ti element enters the lattice to form second phase particles with different crystal structures. The second phase particles can be in a coherent or incoherent relationship with the matrix, hindering the movement of dislocations and enhancing the strength of the material, thereby further improving the strength of the positive electrode material and improving the cycle deterioration caused by particle crushing, so that the sodium positive electrode material has a higher cycle stability.

[0045] At the same time, since iron is a variable-valence element, accompanied by the Jan-Taylor effect, during the charge and discharge process, iron is easily separated from the main body and participates in the charge and discharge process (self-discharge), and some iron will be reduced and precipitated at the negative electrode. The introduction of Ti can inhibit the migration of iron to a high-valence state, inhibit the Jan-Taylor effect, stabilize iron in the transition metal layer, and reduce the amount of iron precipitated at the negative electrode during the charge and discharge process. Due to the low conductivity of Ti, iron can be further passivated, making it difficult for iron to precipitate.

[0046] However, due to the low conductivity of Ti, the introduction of Ti will reduce the conductivity of the sodium cathode material. At this time, since Cu and Ag are materials with good conductivity (specifically, the metal electronic conductivity is greater than 30*10 6 s / m), introducing the above metal elements into the material surface can induce electron tunneling effect, improve the electronic conductivity of the positive electrode material, and make the sodium positive electrode material of the present invention have higher conductivity.

[0047] According to the molecular formula of the sodium positive electrode material, if the X element is uniformly distributed inside the sodium positive electrode material, the mass proportion of the X element in the sodium positive electrode material is about 0.05wt%. In the sodium positive electrode material provided by the present invention, the surface mass proportion of the X element in the sodium positive electrode material is 0.5wt%-2wt%, which means that the X element is more distributed on the surface of the sodium positive electrode material, rather than uniformly distributed inside the sodium positive electrode material. Since the metal electron conductivity of the X element is greater than 30*10 6 s / m, the above distribution makes the sodium positive electrode material provided by the present invention have stronger conductivity.

[0048] The sodium battery positive electrode material provided by the invention has the characteristics of high initial discharge capacity, electrical conductivity and cycle stability.

[0049] Specifically, the first discharge capacity of the sodium-based positive electrode material provided by the present invention is greater than or equal to 130 mAh / g; and / or, the powder resistance under a pressure of 18 MPa is less than or equal to 320,000 Ω*cm; and / or, after the full battery including the positive electrode material is cycled 100 times in a 45°C environment, the capacity retention rate is greater than or equal to 94.5%, and the amount of Fe element dissolved in the negative electrode is less than or equal to 50 ppm. This further illustrates that the present invention has the characteristics of high first discharge capacity, conductivity and cycle stability. The Fe element is a component of the positive electrode. A large amount of Fe element is dissolved, which means that the positive electrode structure is damaged, and the cycle will deteriorate rapidly at this time. Therefore, the amount of Fe element dissolved in the negative electrode is less than or equal to 50 ppm, which means that the sodium-based positive electrode material has high cycle stability.

[0050] More specifically, the single-particle compressive strength of the sodium-based positive electrode material provided by the present invention is greater than or equal to 190MPa, which indicates that the sodium-based positive electrode material has high mechanical strength. Furthermore, the sodium-based positive electrode material also has the characteristic of Dv3 being greater than 2μm. Dv3 is a volume particle size index, that is, the particle size value that accounts for 3% of the volume in the positive electrode material. This index characterizes whether the material contains fine powder. Fine powder has a large specific surface area, is difficult to process, is highly active, and has more intense side reactions with the electrolyte, affecting the cycle stability. Dv3 being greater than 2μm indicates that the volume proportion of fine powder with a particle size of less than 2μm in the sodium-based positive electrode material is less than 3%. The small volume proportion of fine powder makes the sodium-based positive electrode material provided by the present invention have higher initial discharge capacity, conductivity and cycle stability.

[0051] In a specific embodiment, in the dQ / dV spectrum measured after the full battery including the positive electrode material is cycled for 100 cycles in a 45°C environment, no irreversible phase change occurs in the 3.7-4V range. The occurrence of phase transition indicates that the cycle stability of the positive electrode material is reduced. Therefore, in the dQ / dV spectrum measured after the full battery including the positive electrode material is cycled for 100 cycles in a 45°C environment, no irreversible phase change occurs in the 3.7-4V range, indicating that the higher cycle stability feature of the positive electrode material provided by the present invention is more prominent. Furthermore, in one embodiment, the average voltage of the button battery 2-4V including the sodium-based positive electrode material provided by the present invention is greater than or equal to 3.1V, which indicates that the positive electrode material provided by the present invention further has the characteristic of higher voltage balancing.

[0052] In one embodiment, under SEM (5K field of view), the sodium positive electrode material provided by the present invention is observed by SEM, and the number of fine powders irregularly adsorbed on the surface of conventional particles is less than 20. The above phenomenon also shows that there are fewer fine powders in the sodium positive electrode material provided by the present invention, so that the sodium positive electrode material provided by the present invention has more prominent characteristics of higher initial discharge capacity, conductivity and cycle stability.

[0053] The second aspect of the present invention provides a method for preparing a sodium positive electrode material, which can be used to prepare the sodium positive electrode material provided by the first aspect of the present invention. The preparation method comprises the following steps:

[0054] 1) performing a first sintering treatment on a mixed system including a nickel iron manganese oxide precursor, a titanium source and a sodium source to obtain a first sintered product;

[0055] 2) performing a second sintering treatment on the mixed system including the first sintered product and the X element metal source to obtain a sodium positive electrode material;

[0056] The first sintering treatment has a treatment temperature of 850-1000°C and a holding time of 8-14h;

[0057] The treatment temperature of the second sintering treatment is 400-800°C, and the holding time is 6-12h.

[0058] Among them, the general formula of nickel iron manganese oxide precursor is Ni b Fe d Mn e (OH)2, 0.20≤b≤0.30, 0.3≤d≤0.4, 0.3≤e≤0.5.

[0059] The present invention does not limit the preparation method of the nickel iron manganese oxide precursor, and the nickel iron manganese oxide precursor can be prepared by a commonly used preparation method in the art, such as a co-precipitation method.

[0060] Add pure water, 12% ammonia water and 30% sodium hydroxide solution into the reactor and stir at a stirring speed of 200 r / min to obtain a bottom liquid. 3 / h flow rate of nitrogen, the total volume of the bottom liquid is 3.5m 3 , the ammonia concentration of the bottom solution is 2g / L;

[0061] Coprecipitation reaction: add a nickel-iron-manganese mixed solution (including an aqueous solution of nickel ions, iron ions and manganese ions), alkali solution and ammonia water into a reactor, carry out a coprecipitation reaction at a temperature of 45°C, react for 100 hours, and obtain a nickel-iron-manganese hydroxide slurry; the molar ratio of nickel, iron and manganese elements in the nickel-iron-manganese mixed solution is 25:35:40, the total concentration of the nickel-iron-manganese mixed solution is 80g / L, and the flow rate is 200L / h; the concentration of the sodium hydroxide solution is 20%, and the flow rate is 50L / h; the mass concentration of the ammonia water is 12%, and the flow rate is 10L / h;

[0062] Post-processing: The nickel-iron-manganese hydroxide slurry is washed, dried, screened and packaged in sequence to obtain a nickel-iron-manganese-sodium ternary precursor.

[0063] The titanium source is a compound containing titanium. In the preparation method provided by the present invention, the titanium source is selected from at least one of titanium dioxide, titanium boride, titanium carbide, and titanate (eg, alkali metal titanate).

[0064] The sodium source is a compound containing sodium. In the preparation method provided by the present invention, the sodium source is at least one of sodium carbonate, sodium bicarbonate, sodium acetate and sodium oxalate.

[0065] The X element metal source is a compound containing the X element. The preparation method provided by the present invention does not limit the specific selection of the X element metal source, as long as it meets the requirement of including the X element. For example, when the X element is copper, the X element metal source can be selected from at least one of copper sulfate, copper chloride, copper nitrate, and copper acetate; when the X element is silver, the X element metal source can be selected from silver nitrate.

[0066] In the preparation method provided by the present invention, the molar ratio of the nickel iron manganese oxide precursor, the titanium source and the sodium source can be referred to the general formula of the sodium positive electrode material Na a Ni b Ti c Fe d Mn e X f O2, wherein 0.94≤a≤1.04, 0.20≤b≤0.30, 0.03≤c≤0.1, 0.3≤d≤0.4, 0.3≤e≤0.5, 0.001≤f≤0.02. That is, first select the values ​​of a, b, c, d, e, and f, prepare the nickel iron manganese oxide precursor according to the values ​​of b, d, and e, and then use the values ​​of a, c, and f to determine the amount of sodium source, titanium source, and X element metal source. The mixed system composed of raw materials meeting the above molar ratio is subjected to a first sintering treatment to obtain a first sintered product. In the preparation method provided by the present invention, the treatment temperature of the first sintering treatment is 850-1000°C, and the holding time is 8-14h. Among them, the holding time refers to the duration of the target treatment temperature, and does not include the time required for the initial temperature to rise to the target treatment temperature. The present invention does not limit the heating rate from the initial temperature to the target treatment temperature, and the heating rate commonly used in the art can be used. The above process can make the product have a better crystallization effect, so that the positive electrode material obtained has more outstanding anti-breakage performance during the cycle process.

[0067] Furthermore, the first sintering process may be performed in an air atmosphere, and oxygen contained in the air is helpful for forming the first sintered product.

[0068] Furthermore, the first sintered product is mixed with an X element metal source and subjected to a second sintering treatment to obtain a second sintered product. The amount of the X element metal source added can be referred to above and will not be repeated here. In the preparation method provided by the present invention, the treatment temperature of the second sintering treatment is 400-800°C and the insulation time is 6-12h. The above-mentioned treatment conditions can further improve the structural instability caused by the excessive introduction of Fe, while promoting recrystallization and improving internal stress, so that the obtained positive electrode material has more outstanding anti-crushing performance during the cycle.

[0069] Furthermore. The first sintered product is mixed with a metal source of the X element, and the X element is introduced in the latter sintering during the second sintering treatment. Unlike the introduction of the X element in the precursor preparation stage, when the X element is introduced in the precursor preparation stage, the X element can enter the crystal lattice and participate in the construction of the transition metal layer; when the X element is introduced in the latter sintering, X does not enter the crystal lattice, but is coated on the surface of the first sintered product, thereby improving the electronic conductivity. The above content can be verified by the fact that the surface mass of the X element in the sodium positive electrode material accounts for 0.5-2wt%.

[0070] The method for preparing the sodium battery positive electrode material provided by the present invention uses common raw materials and simple steps to prepare the sodium battery positive electrode material with high energy density, conductivity and cycle stability, and has the characteristic of simple operation.

[0071] In one embodiment, the first sintering treatment includes first heating to 600-700°C at a heating rate of 4-8°C / min, then heating to 850-1000°C at a heating rate of 1-2°C / min, and keeping warm for 8-14h. The preparation method provided by the present invention limits the heating curve of the first sintering treatment to fast first and slow later, and the introduction of Ti and the heating of the nucleation temperature to 850-1000°C at a heating rate of 1-2°C / min act together to slow down the nucleation of the crystal structure, and the unit cell will be more uniform and have better consistency, so that the internal stress of the obtained positive electrode material during the cycle process is smaller and has higher particle compressive strength.

[0072] Further, in one embodiment, the second sintering treatment includes heating to 400-800°C at a heating rate of 1-5°C / min and keeping the temperature for 6-12 hours. The above heating rate can slow down the nucleation of the crystal structure, and the unit cell will be more uniform and have better consistency, so that the internal stress of the obtained positive electrode material during the cycle process is smaller, and the characteristics of higher compressive strength of the particles are further enhanced.

[0073] Furthermore, in one embodiment, the product obtained by the first sintering process is cooled to room temperature at a rate of 2-5°C / min. The above cooling rate can reduce the internal stress of the positive electrode material during the cycle, and further enhance the high compressive strength of the particles.

[0074] In one embodiment, the X element metal source is selected from at least one of copper oxide and silver oxide. The above compound as the X element metal source can be better integrated with other raw materials, so that the energy density, conductivity and cycle stability of the prepared sodium positive electrode material are more prominent.

[0075] The third aspect of the present invention provides a positive electrode sheet, which includes the sodium battery positive electrode material provided by the first aspect of the present invention.

[0076] The positive electrode sheet of the present invention specifically includes a positive electrode current collector and a positive electrode active layer formed of a positive electrode active material and arranged on the surface of the positive electrode current collector.

[0077] The present invention does not limit the preparation method of the positive electrode sheet, and it can be prepared using the common methods in the art. In one embodiment, the sodium positive electrode material and binder provided by the present invention can be dispersed in an appropriate amount of N-methylpyrrolidone (NMP) solvent, and fully stirred and mixed to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode collector, and the positive electrode sheet is obtained after drying, rolling and slitting. In a specific embodiment, the positive electrode active layer includes 70-99wt% of positive electrode active material, 0.5-15wt% of conductive agent, and 0.5-15wt% of binder according to the mass percentage, and further includes 80-98wt% of positive electrode active material, 1-10wt% of conductive agent, and 1-10wt% of binder.

[0078] Among them, the material of the positive electrode current collector can be at least one of aluminum foil, carbon-coated aluminum foil, copper foil and nickel foil; the binder can be selected from at least one of fluorine-containing resin, polyether resin, cellulose type binder, polyacrylate type binder and polyimide.

[0079] Since the sodium battery positive electrode material provided by the present invention has the characteristic of high discharge specific capacity, the positive electrode sheet provided by the present invention also has the characteristic of high discharge specific capacity.

[0080] The fourth aspect of the present invention provides a battery, which includes any one of the sodium battery positive electrode materials provided by the first aspect of the present invention, or includes any one of the positive electrode sheets provided by the third aspect of the present invention.

[0081] It is conceivable that the battery provided by the present invention includes, in addition to the above-mentioned positive electrode sheet, a negative electrode sheet, an electrolyte and a separator.

[0082] The present invention does not strictly limit the negative electrode active material in the negative electrode sheet, and can be at least one of the negative electrode active materials commonly used in sodium ion batteries, such as sodium sheets, graphite, hard carbon, soft carbon, mesophase carbon microspheres, silicon-based negative electrode materials (mainly including silicon oxide, silicon-carbon negative electrode), tin-based negative electrode materials (mainly including tin, tin alloys), etc.

[0083] The present invention does not strictly limit the choice of electrolyte, which may include one or more of the solvents commonly used in sodium ion battery electrolytes, for example, at least one of the solutions of propylene carbonate and / or ethylene carbonate of NaPF6 and / or NaClO4.

[0084] The present invention does not strictly limit the material selection of the diaphragm, and it can be a diaphragm material commonly used in current sodium ion batteries, such as at least one selected from polypropylene, polyethylene, and glass fiber.

[0085] The battery provided by the invention has the characteristic of high discharge specific capacity.

[0086] The sodium positive electrode material provided by the present invention and its preparation method and application are further described below through examples.

[0087] First, the nickel iron manganese oxide precursor was prepared by the following method:

[0088] 1) Add pure water, 12% ammonia water and 30% sodium hydroxide solution into the reactor and stir. Control the stirring speed to 200r / min to obtain the bottom liquid. At the same time, add 0.6m 3 / h flow rate of nitrogen, the total volume of the bottom liquid is 3.5m 3 , the ammonia concentration of the bottom solution is 2g / L;

[0089] 2) Coprecipitation reaction: adding a nickel-iron-manganese mixed solution, an alkali solution and an ammonia solution to a reactor, and carrying out a coprecipitation reaction at a temperature of 45° C. for 100 hours to obtain a nickel-iron-manganese hydroxide slurry; the molar ratio of nickel, iron and manganese elements in the nickel-iron-manganese mixed solution is 25:35:40, the total concentration of the nickel-iron-manganese mixed solution is 80 g / L, and the flow rate is 200 L / h; the concentration of the sodium hydroxide solution is 20%, and the flow rate is 50 L / h; the mass concentration of the ammonia solution is 12%, and the flow rate is 10 L / h;

[0090] 3) Post-treatment: The nickel-iron-manganese hydroxide slurry is sequentially washed, dried, screened and packaged to obtain a nickel-iron-manganese-sodium ternary precursor.

[0091] The molar ratio of nickel, iron and manganese in the iron-manganese mixed solution in step 2) can be changed according to the general formula of the precursor to be obtained. 0.25 Fe 0.35 Mn 0.40 (OH)2 precursor, the molar ratio of nickel, iron, and manganese is 25:35:40. 0.25 Fe 0.25 Mn 0.50 (OH)2 precursor, the molar ratio of nickel, iron and manganese elements is 25:25:50.

[0092] Example 1

[0093] Add 10kg of Ni into the high-speed mixer. 0.25 Fe 0.35 Mn 0.40 (OH)2, 6.04 kg Na 2C O3 and 100.6g TiO2 were stirred and mixed in a 50L high mixer at 900rpm for 10min, the mixture was placed in a sagger, air atmosphere was introduced, the temperature was first raised to 650℃ at 6℃ / min, then raised to 940℃ at 1.5℃ / min and kept warm for 10h for sintering, and then cooled to room temperature at a rate of 3℃ / min by water cooling and exhaust fan. The materials out of the furnace were crushed and sieved with a jet mill. The crushed material and 53.9g Ag2O were then stirred and mixed in a 30L high mixer at 900rpm for 10min, the mixture was placed in a sagger, air atmosphere was introduced, the temperature was raised to 600℃ at 3℃ / min and kept warm for 10h, and then cooled with the furnace. The materials out of the furnace were sieved, iron-removed and packaged to obtain a molecular formula of NaNi 0.25 Fe 0.35 Mn 0.40 Ti 0.006 Ag 0.005 Sodium O2 layered cathode materials.

[0094] Example 2

[0095] Add 10kg of Ni into the high-speed mixer. 0.25 Fe 0.35 Mn 0.40 (OH)2, 6.04kg Na2CO3 and 100.6g TiO2 were stirred and mixed in a 50L high mixer at 900rpm for 10min, and the mixture was placed in a sagger, and air atmosphere was introduced. The temperature was first raised to 650℃ at 6℃ / min, and then raised to 940℃ at 1.5℃ / min and kept warm for 10h for sintering. After that, the material was cooled to room temperature at a rate of 3℃ / min by water cooling and exhaust fan. The material after being taken out of the furnace was crushed and sieved with a jet mill. Then, the crushed material and 63.5CuO were stirred and mixed in a 30L high mixer at 900rpm for 10min, and the mixture was placed in a sagger, and air atmosphere was introduced. The temperature was raised to 600℃ at 3℃ / min and kept warm for sintering for 10h, and then cooled with the furnace. The material after being taken out of the furnace was sieved, deironed and packaged (by setting the current size to 20-30A, a magnetic field was formed to remove iron (magnetic foreign matter), and the rest is the same), and the molecular formula was obtained. NaNi 0.25 Fe 0.35 Mn 0.40 Ti 0.006 Cu 0.005 Sodium-ion layered cathode materials for O2.

[0096] Example 3

[0097] Add 10kg of Ni into the high-speed mixer. 0.25 Fe 0.35 Mn 0.40 (OH)2, 6.04kg Na2CO3 and 100.6g TiO2 were stirred and mixed in a 50L high mixer at 900rpm for 10min, and the mixture was placed in a sagger, and air atmosphere was introduced. The temperature was first raised to 650℃ at 6℃ / min, and then raised to 940℃ at 1.5℃ / min and kept warm for 10h for sintering. After that, the material was cooled to room temperature at a rate of 3℃ / min by means of water cooling and exhaust fan. The material after being taken out of the furnace was crushed and sieved with a jet mill. The crushed material and 31.8g CuO and 27.0g Ag2O were then stirred and mixed in a 30L high mixer at 900rpm for 10min. The mixture was placed in a sagger, and air atmosphere was introduced. The temperature was raised to 600℃ at 3℃ / min and kept warm for sintering for 10h. After that, the material was cooled with the furnace. The material after being taken out of the furnace was sieved, iron-removed and packaged to obtain the molecular formula

[0098] NeNi 0.25 Fe 0.35 Mn 0.40 Ti 0.006 Ag 0.0025 Cu 0.0025 Sodium-ion layered cathode materials for O2.

[0099] Example 4

[0100] Add 10kg of Ni into the high-speed mixer. 0.25 Fe 0.30 Mn 0.45 (OH)2, 6.04kg Na2CO3 and 100.6g TiO2 were stirred and mixed in a 50L high mixer at 900rpm for 10min, the mixture was placed in a sagger, air atmosphere was introduced, the temperature was first raised to 650℃ at 6℃ / min, then raised to 940℃ at 1.5℃ / min and kept warm for 10h for sintering, and then cooled to room temperature at a rate of 3℃ / min by water cooling and exhaust fan. The material after being taken out of the furnace was crushed and sieved with a jet mill. The crushed material and 53.9g Ag2O were then stirred and mixed in a 30L high mixer at 900rpm for 10min, the mixture was placed in a sagger, air atmosphere was introduced, the temperature was raised to 600℃ at 3℃ / min and kept warm for 10h, and then cooled with the furnace. The material after being taken out of the furnace was sieved, iron removed and packaged to obtain a molecular formula of

[0101] NeNi 0.25 Fe 0.35 Mn 0.40 Ti 0.006 Ag 0.005Sodium O2 layered cathode materials.

[0102] Example 5

[0103] Add 10kg of Ni into the high-speed mixer. 0.25 Fe 0.40 Mn 0.35 (OH)2, 6.04kg Na2CO3 and 100.6g TiO2 were stirred and mixed in a 50L high mixer at 900rpm for 10min, the mixture was placed in a sagger, air atmosphere was introduced, the temperature was first raised to 650℃ at 6℃ / min, then raised to 940℃ at 1.5℃ / min and kept warm for 10h for sintering, and then cooled to room temperature at a rate of 3℃ / min by water cooling and exhaust fan. The material after being taken out of the furnace was crushed and sieved with a jet mill. The crushed material and 53.9g Ag2O were then stirred and mixed in a 30L high mixer at 900rpm for 10min, the mixture was placed in a sagger, air atmosphere was introduced, the temperature was raised to 600℃ at 3℃ / min and kept warm for 10h, and then cooled with the furnace. The material after being taken out of the furnace was sieved, iron removed and packaged to obtain a molecular formula of

[0104] NeNi 0.25 Fe 0.35 Mn 0.40 Ti 0.006 Ag 0.005 Sodium-ion layered cathode materials for O2.

[0105] Example 6

[0106] Add 10kg of Ni into the high-speed mixer. 0.25 Fe 0.35 Mn 0.40 (OH)2, 6.04kg Na2CO3 and 100.6g TiO2 were stirred and mixed in a 50L high mixer at 900rpm for 10min, the mixture was placed in a sagger, air atmosphere was introduced, the temperature was first raised to 650℃ at 4℃ / min, then raised to 940℃ at 1℃ / min and kept warm for 10h for sintering, and then cooled to room temperature at a rate of 3℃ / min by water cooling and exhaust fan. The materials out of the furnace were crushed and sieved with a jet mill. The crushed material and 53.9g Ag2O were then stirred and mixed in a 30L high mixer at 900rpm for 10min, the mixture was placed in a sagger, air atmosphere was introduced, the temperature was raised to 600℃ at 3℃ / min and kept warm for 10h, and then cooled with the furnace. The materials out of the furnace were sieved, iron-removed and packaged to obtain the molecular formula

[0107] NeNi 0.25 Fe 0.35 Mn 0.40 Ti 0.006 Ag 0.005Sodium-ion layered cathode materials for O2.

[0108] Example 7

[0109] Add 10kg of Ni into the high-speed mixer. 0.25 Fe 0.35 Mn 0.40 (OH)2, 6.04kg Na2CO3 and 100.6g TiO2 were stirred and mixed in a 50L high mixer at 900rpm for 10min, and the mixture was placed in a sagger, and air atmosphere was introduced. The temperature was first raised to 650℃ at 8℃ / min, and then raised to 940℃ at 2℃ / min and kept warm for 10h for sintering. After that, the material was cooled to room temperature at a rate of 3℃ / min by means of water cooling and exhaust fan. The material after being taken out of the furnace was crushed and sieved with a jet mill. The crushed material and 53.9g Ag2O were then stirred and mixed in a 30L high mixer at 900rpm for 10min, and the mixture was placed in a sagger, and air atmosphere was introduced. The temperature was raised to 600℃ at 3℃ / min and kept warm for 10h, and then cooled with the furnace. The material after being taken out of the furnace was sieved, iron-removed and packaged to obtain the molecular formula

[0110] NeNi 0.25 Fe 0.35 Mn 0.40 Ti 0.006 Ag 0.005 Sodium-ion layered cathode materials for O2.

[0111] Example 8

[0112] Add 10kg of Ni into the high-speed mixer. 0.25 Fe 0.35 Mn 0.40 (OH)2, 6.04kg Na2CO3 and 100.6g TiO2 were stirred and mixed in a 50L high mixer at 900rpm for 10min, the mixture was placed in a sagger, air atmosphere was introduced, the temperature was first raised to 650℃ at 1.5℃ / min, then raised to 940℃ at 1.5℃ / min and kept warm for 10h for sintering, and then cooled to room temperature at a rate of 3℃ / min by means of water cooling and exhaust fan. The materials out of the furnace were crushed and sieved with a jet mill. The crushed material and 53.9g Ag2O were then stirred and mixed in a 30L high mixer at 900rpm for 10min, the mixture was placed in a sagger, air atmosphere was introduced, the temperature was raised to 600℃ at 3℃ / min and kept warm for sintering for 10h, and then cooled with the furnace. The materials out of the furnace were sieved, iron removed and packaged to obtain the molecular formula

[0113] NeNi 0.25 Fe 0.35 Mn 0.40 Ti 0.006 Ag 0.005Sodium-ion layered cathode materials for O2.

[0114] Example 9

[0115] Add 10kg of Ni into the high-speed mixer. 0.25 Fe 0.35 Mn 0.40 (OH)2, 6.04kg Na2CO3 and 100.6g TiO2 were stirred and mixed in a 50L high mixer at 900rpm for 10min, the mixture was placed in a sagger, air atmosphere was introduced, the temperature was first raised to 650℃ at 6℃ / min, then raised to 940℃ at 6℃ / min and kept warm for 10h for sintering, and then cooled to room temperature at a rate of 3℃ / min by means of water cooling and exhaust fan. The materials out of the furnace were crushed and sieved with a jet mill. The crushed material and 53.9g Ag2O were then stirred and mixed in a 30L high mixer at 900rpm for 10min, the mixture was placed in a sagger, air atmosphere was introduced, the temperature was raised to 600℃ at 3℃ / min and kept warm for 10h, and then cooled with the furnace. The materials out of the furnace were sieved, iron-removed and packaged to obtain the molecular formula

[0116] NeNi 0.25 Fe 0.35 Mn 0.40 Ti 0.006 Ag 0.005 Sodium-ion layered cathode materials for O2.

[0117] Example 10

[0118] Add 10kg of Ni into the high-speed mixer. 0.28 Fe 0.32 Mn 0.40 (OH)2, 6.04 kg Na 2C O3 and 100.6g TiO2 were stirred and mixed in a 50L high mixer at 900rpm for 10min, the mixture was placed in a sagger, air atmosphere was introduced, the temperature was first raised to 650℃ at 6℃ / min, then raised to 940℃ at 1.5℃ / min and kept warm for 10h for sintering, and then cooled to room temperature at a rate of 3℃ / min by water cooling and exhaust fan. The materials out of the furnace were crushed and sieved with a jet mill. The crushed material and 53.9g Ag2O were then stirred and mixed in a 30L high mixer at 900rpm for 10min, the mixture was placed in a sagger, air atmosphere was introduced, the temperature was raised to 600℃ at 3℃ / min and kept warm for 10h, and then cooled with the furnace. The materials out of the furnace were sieved, iron-removed and packaged to obtain a molecular formula of NaNi 0.28 Fe 0.32 Mn 0.40 Ti 0.006 Ag 0.005 Sodium-ion layered cathode materials for O2.

[0119] Embodiment 11

[0120] Add 10kg of Ni into the high-speed mixer. 0.25 Fe 0.35 Mn 0.40 (OH)2, 5.80kg Na 2C O3 and 100.6g TiO2 were stirred and mixed in a 50L high mixer at 900rpm for 10min, and the mixture was placed in a sagger, and air atmosphere was introduced. The temperature was first raised to 650℃ at 6℃ / min, and then raised to 940℃ at 1.5℃ / min and kept warm for 10h for sintering. After that, the material was cooled to room temperature at a rate of 3℃ / min by water cooling and exhaust fan. The material after the furnace was crushed and sieved with a jet mill. The crushed material and 53.9g Ag2O were stirred and mixed in a 30L high mixer at 900rpm for 10min, and the mixture was placed in a sagger, and air atmosphere was introduced. The temperature was raised to 600℃ at 3℃ / min and kept warm for sintering for 10h, and then cooled with the furnace. The material after the furnace was sieved, iron-removed and packaged to obtain a molecular formula of Na 0.96 Ni 0.25 Fe 0.35 Mn 0.40 Ti 0.006 Ag 0.005 Sodium-ion layered cathode materials for O2.

[0121] Comparative Example 1

[0122] Add 10kg of Ni into the high-speed mixer. 0.25 Fe 0.35 Mn 0.40 (OH)2 and 6.04kg Na2CO3 were stirred and mixed in a 50L high mixer at 900rpm for 10min, and the mixture was placed in a sagger and introduced into an air atmosphere. The temperature was first raised to 650℃ at 6℃ / min, and then raised to 940℃ at 1.5℃ / min and kept warm for 10h for sintering. After that, the material was cooled to room temperature at a rate of 3℃ / min by means of water cooling and exhaust fan. The material after being taken out of the furnace was crushed and sieved with a jet mill. The crushed material and 53.9g Ag2O were then stirred and mixed in a 30L high mixer at 900rpm for 10min. The mixture was placed in a sagger and introduced into an air atmosphere. The temperature was raised to 600℃ at 3℃ / min and kept warm for sintering for 10h. After that, it was cooled with the furnace. The material after being taken out of the furnace was sieved, iron-removed and packaged to obtain a material with the molecular formula of NaNi 0.25 Fe 0.35 Mn 0.40 Ag 0.005 Sodium-ion layered cathode materials for O2.

[0123] Comparative Example 2

[0124] Add 10kg of Ni into the high-speed mixer. 0.25 Fe 0.35 Mn 0.40 (OH)2, 6.04kg Na2CO3 and 83.2gMgO were stirred and mixed in a 50L high mixer at 900rpm for 10min, and the mixture was placed in a sagger, and air atmosphere was introduced. The temperature was first raised to 650℃ at 6℃ / min, and then raised to 940℃ at 1.5℃ / min and kept warm for 10h for sintering. Then, the material was cooled to room temperature at a rate of 3℃ / min by water cooling and exhaust fan. The material after being taken out of the furnace was crushed and sieved with a jet mill. Then, the crushed material and 53.9gAg2O were stirred and mixed in a 30L high mixer at 900rpm for 10min, and the mixture was placed in a sagger, and air atmosphere was introduced. The temperature was raised to 600℃ at 3℃ / min and kept warm for sintering for 10h. Then, the material was cooled with the furnace. The material after being taken out of the furnace was sieved, iron-removed and packaged to obtain a material with the molecular formula of NaNi 0.25 Fe 0.35 Mn 0.40 Mg 0.005 Ag 0.005 Sodium-ion layered cathode materials for O2.

[0125] Comparative Example 3

[0126] Add 10kg of Ni into the high-speed mixer. 0.25 Fe 0.35 Mn 0.40 (OH)2, 6.04kg Na2CO3 and 100.6g TiO2 were stirred and mixed in a 50L high mixer at 900rpm for 10min, and the mixture was placed in a sagger and introduced into an air atmosphere. The temperature was first raised to 650℃ at 6℃ / min, and then raised to 940℃ at 1.5℃ / min and kept warm for 10h for sintering. After that, the material was cooled to room temperature at a rate of 3℃ / min by means of water cooling and exhaust fan. The material after being taken out of the furnace was crushed and sieved with a jet mill. The crushed material was then placed in a sagger, introduced into an air atmosphere, and heated to 600℃ at 3℃ / min and kept warm for 10h. After that, it was cooled with the furnace. The material after being taken out of the furnace was sieved, iron removed and packaged to obtain a molecular formula of

[0127] NeNi 0.25 Fe 0.35 Mn 0.40 Ti 0.006 Sodium-ion layered cathode materials for O2.

[0128] Comparative Example 4

[0129] Add 10kg of Ni into the high-speed mixer. 0.25 Fe 0.35 Mn 0.40(OH)2, 6.04kg Na2CO3 and 100.6g TiO2 were stirred and mixed in a 50L high mixer at 900rpm for 10min, the mixture was placed in a sagger, air atmosphere was introduced, the temperature was first raised to 650℃ at 6℃ / min, then raised to 940℃ at 1.5℃ / min and kept warm for 10h for sintering, and then cooled to room temperature at a rate of 3℃ / min by means of water cooling and exhaust fan. The materials out of the furnace were crushed and sieved with a jet mill. The crushed material and 67.7g ZrO2 were then stirred and mixed in a 30L high mixer at 900rpm for 10min, the mixture was placed in a sagger, air atmosphere was introduced, the temperature was raised to 600℃ at 3℃ / min and kept warm for 10h, and then cooled with the furnace. The materials out of the furnace were sieved, iron-removed and packaged to obtain the molecular formula

[0130] NeNi 0.25 Fe 0.35 Mn 0.40 Ti 0.006 Zr 0.005 Sodium-ion layered cathode materials for O2.

[0131] Comparative Example 5

[0132] Add 10kg of Ni into the high-speed mixer. 0.25 Fe 0.25 Mn 0.50 (OH)2, 6.04kg Na2CO3 and 100.6g TiO2 were stirred and mixed in a 50L high mixer at 900rpm for 10min, the mixture was placed in a sagger, air atmosphere was introduced, the temperature was first raised to 650℃ at 6℃ / min, then raised to 940℃ at 1.5℃ / min and kept warm for 10h for sintering, and then cooled to room temperature at a rate of 3℃ / min by water cooling and exhaust fan. The material after being taken out of the furnace was crushed and sieved with a jet mill. The crushed material and 53.9g Ag2O were then stirred and mixed in a 30L high mixer at 900rpm for 10min, the mixture was placed in a sagger, air atmosphere was introduced, the temperature was raised to 600℃ at 3℃ / min and kept warm for 10h, and then cooled with the furnace. The material after being taken out of the furnace was sieved, iron removed and packaged to obtain a molecular formula of

[0133] NeNi 0.25 Fe 0.25 Mn 0.50 Ti 0.006 Ag 0.005 Sodium-ion layered cathode materials for O2.

[0134] Comparative Example 6

[0135] Add 10kg of Ni into the high-speed mixer. 0.25 Fe 0.45 Mn 0.30(OH)2, 6.04kg Na2CO3 and 100.6g TiO2 were stirred and mixed in a 50L high mixer at 900rpm for 10min, the mixture was placed in a sagger, air atmosphere was introduced, the temperature was first raised to 650℃ at 6℃ / min, then raised to 940℃ at 1.5℃ / min and kept warm for 10h for sintering, and then cooled to room temperature at a rate of 3℃ / min by water cooling and exhaust fan. The material after being taken out of the furnace was crushed and sieved with a jet mill. The crushed material and 53.9g Ag2O were then stirred and mixed in a 30L high mixer at 900rpm for 10min, the mixture was placed in a sagger, air atmosphere was introduced, the temperature was raised to 600℃ at 3℃ / min and kept warm for 10h, and then cooled with the furnace. The material after being taken out of the furnace was sieved, iron removed and packaged to obtain a molecular formula of

[0136] NeNi 0.25 Fe 0.45 Mn 0.30 Ti 0.006 Ag 0.005 Sodium-ion layered cathode materials for O2.

[0137] Comparative Example 7

[0138] Add 10kg of Ni into the high-speed mixer. 0.25 Fe 0.35 Mn 0.40 (OH)2, 6.04 kg Na 2C O3 and 100.6g TiO2 and 53.9g Ag2O were stirred and mixed in a 50L high mixer at 900rpm for 10min, and the mixture was placed in a sagger, and air atmosphere was introduced. The temperature was first raised to 650℃ at 6℃ / min, and then raised to 940℃ at 1.5℃ / min and kept warm for 10h for heat preservation and sintering. After that, the material was cooled to room temperature at a rate of 3℃ / min by water cooling and exhaust fan. The material after being taken out of the furnace was crushed and sieved by air flow mill. The crushed material was then placed in a sagger, and air atmosphere was introduced. The temperature was raised to 600℃ at 3℃ / min and kept warm for 10h, and then cooled with the furnace. The material after being taken out of the furnace was sieved, iron removed and packaged to obtain the molecular formula

[0139] NeNi 0.25 Fe 0.35 Mn 0.40 Ti 0.006 Ag 0.005 Sodium-ion layered cathode materials for O2.

[0140] Test example

[0141] 1. SEM test was performed on the sodium positive electrode materials prepared in Example 1, Example 2 and Comparative Example 1, and the results were as follows: Figure 1-Figure 3 ;

[0142] Depend on Figure 1-Figure 3 It can be seen that Figure 3 In the comparative example 1, there are fine particles on the surface of the sodium positive electrode material. EDS analysis of the fine particles shows that the fine particles are sodium compounds. It can be seen that since no Ti element is added in comparative example 1, sodium compounds are precipitated on the surface of the obtained sodium positive electrode material. The sodium compound can become a residual alkali, which affects the gas production and processing performance of the positive electrode material.

[0143] The sodium positive electrode material prepared in Example 1 was subjected to XRD test, and the image is shown in Figure 4 . Figure 4 By referring to the peak shape of PDF standard card 28-0819-NaCrO2, it can be seen that this material is a layered O3 sodium cathode material.

[0144] 2. The single particle strength, powder resistance and Dv3 of the sodium electrode layered positive electrode materials prepared in each embodiment and comparative example were tested. The results are shown in Table 1.

[0145] in:

[0146] The test method for the particle strength of a single particle is as follows: Using Shimadzu DUH-211S equipment, under a 500x microscope, select a single particle with a primary particle size distribution of 3-8μm in the positive electrode material, apply pressure with a 50μm flat pressure head, record the corresponding pressure and pressure, and obtain the pressure corresponding to the particle crushing. Test more than 10 particles and take the average value.

[0147] Powder resistance test method: Use PD-51 test equipment, MCP-T700 impedance meter, and four-probe method. Weigh 4g of material and place it in a measuring cylinder with a radius of 10mm. Record the powder resistance value under a pressure of 18MPa.

[0148] Test method of Dv3: Use Malvern 3000 particle size tester, add about 0.2g of sample in a 50mL beaker, add 1 dropper of 10% sodium hexametaphosphate, add water to about 20mL, and perform external ultrasound at 60% intensity for 5 minutes. Then transfer to a beaker of 1L deionized water, stir at 3000rpm, and perform the test at 8-12% light shielding.

[0149] The test method for the mass ratio of X element in the surface of sodium positive electrode material is as follows: ion milling is performed using Gatan 697Ilion II equipment, the outlet pressure of high-purity argon is controlled at 0.18MPa, the pressure of the sample chamber is less than 5×10-6Torr, the angles of the left and right guns are controlled at 0 degrees, and the ion beam energy is 5keV. After milling, EDS measurement is performed using Hitachi Regulus 8100 / SU 8010, the test voltage is controlled at 1KV, the test current is 10μA, and the magnification of 10K is used for point scanning. The main elements such as Ni, Fe, Mn, Ti, Cu, and Ag are selected, and the selected different positions (specifically, the spectrum Figure 1 , 2 , 3, and 4 are considered as the surface layer, among which, the spectrum Figure 5 , 6 , 7 are considered as internal) points to automatically calculate the ratio of each element. For the sodium positive electrode material prepared in Example 1, the sampling points are shown in FIG. Figure 5 , the distribution data of silver content at each point can be seen in Figure 6 Take the mass percentage of element X at any surface position of each sample and fill it in Table 1.

[0150] Table 1

[0151]

[0152] It can be seen from Table 1 that the sodium positive electrode materials prepared in Examples 1 to 7 have higher strength and lower resistance than the materials prepared in the comparative examples. In Examples 8 and 9, due to the inappropriate heating rate of the first sintering treatment or the second sintering treatment, the materials prepared have lower strength and higher resistance than the materials prepared in Examples 1 to 7.

[0153] Depend on Figure 6 It can be seen that in the sodium battery positive electrode material prepared in Example 1, the silver element content is higher on the surface of the material, but lower inside the material.

[0154] In Comparative Example 7, silver and titanium are doped simultaneously rather than introduced into the material in the form of post-coating. Compared with Example 1, the surface silver content of the sample prepared in Comparative Example 7 is significantly lower, and the powder resistance is higher. This shows that introducing X element into the positive electrode material in the form of post-coating can enhance the conductivity of the positive electrode material.

[0155] In addition, it can be seen from the foregoing that according to the molecular formula of the sodium positive electrode material, if the X element is uniformly distributed inside the sodium positive electrode material, the mass proportion of the X element in the sodium positive electrode material is about 0.05wt%. As shown in Table 1, in the samples prepared in Examples 1 to 11, the mass proportion of the X element on the surface of the sodium positive electrode material is much higher than 0.05wt%, which indicates that the X element is more distributed on the surface of the sodium positive electrode material, rather than uniformly distributed inside the sodium positive electrode material.

[0156] 3. The sodium layered positive electrode materials prepared in each embodiment and comparative example were assembled into button cells in the following manner:

[0157] The prepared sodium layered cathode material, acetylene black and polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 90:5:5, mixed evenly, added with NMP and stirred for 2 hours to form a viscous slurry, evenly coated on aluminum foil, and then vacuum baked at 80°C, pressed, and cut into cathode sheets with a diameter of 14 mm. A pure sodium sheet with a diameter of 16 mm was used as the anode sheet, Tianci ENA-18 was used as the electrolyte, and a PP / PE / PP composite separator was used to assemble button cells in a glove box filled with argon.

[0158] The assembled button cell was subjected to 0.2C0.2C first discharge capacity, 2-4V average voltage and first efficiency tests. The test results are shown in Table 2.

[0159] Among them, the 0.2C capacity / energy density test method: place the assembled button battery in the blue power equipment, test temperature 25±1℃, test voltage 2.0~4.0V, 0.2C / 0.2C charging & discharging, the charging cut-off current is 0.05C (1C nominal capacity 130mAh / g).

[0160] 2-4V average voltage test method: calculated based on the tested 0.2C charge energy and charge capacity, the calculation method is: 0.2C charge energy / 0.2C charge discharge capacity.

[0161] The test method for the first effect is: at 25°C, charge the battery at a constant current of 0.1C to 4.0V, then charge at a constant voltage to a current less than or equal to 0.01mA, then let it stand for 5 minutes to obtain the charging capacity R1, then discharge at a constant current of 0.1C to 2.0V, then let it stand for 5 minutes to obtain the discharge capacity R2, R2 / R1*100% is the first effect.

[0162] Table 2

[0163]

[0164]

[0165] It can be seen from Table 2 that the sodium battery positive electrode materials prepared in Examples 1 to 11 have higher first discharge capacity, average voltage and first effect than the materials prepared in each comparative example.

[0166] In addition, compared with Examples 1 to 7, the first discharge capacity, average voltage and first efficiency of Examples 8 and 9 are relatively low. This may be due to the slow heating rate of the first sintering treatment during the sample preparation process of Example 8, while the fast heating rate of the first sintering treatment during the sample preparation process of Example 9.

[0167] 4. The sodium-based layered cathode materials prepared in each embodiment and comparative example were assembled into full batteries in the following manner:

[0168] The sodium layered positive electrode material, conductive carbon black SP, conductive graphite KS-6, and binder PVDF were mixed with NMP in a mass ratio of 94.5%: 2%: 1%: 2.5% to prepare positive electrode slurry. The positive electrode slurry was coated (coating density was 12 mg / cm 2 ) and rolling process to make the positive electrode sheet, which is assembled with the negative electrode (graphite), separator (polyCelgard propylene microporous membrane), and electrolyte (1mol / LLiPF6+DEC / EC (volume ratio 1:1)) into a 503048 model full battery with a battery capacity of about 400mAh.

[0169] The assembled full battery was tested for 100 cycles at 45°C and the amount of iron element dissolution at the negative electrode. The results are shown in Table 3.

[0170] The test method for the amount of iron dissolved in the negative electrode is as follows: weigh 0.4g of the negative electrode, which is taken from the full battery after the above-mentioned cycle capacity retention rate test, use 10ml of aqua regia to perform plate digestion, and determine the elements enriched in the negative electrode by ICP-OES equipment.

[0171] The test method for the 45°C 100-cycle capacity retention rate is as follows: use the Xinwei CT3008-5V3A-A1 battery, at 45°C, with a cycle voltage of 4 to 2V and a constant voltage cutoff current of 20mA, and cycle for 100 cycles.

[0172] Cyclic gas production test method: Before cycling, the volume of the soft-pack battery is measured by the water displacement method and recorded as V1. After 100 cycles at 45°C, the volume of the soft-pack battery is measured by the water displacement method and recorded as V2. The volume growth rate is (V2-V1) / V1*100%.

[0173] Table 3

[0174]

[0175] It can be seen from Table 3 that the sodium battery positive electrode materials prepared in Examples 1 to 11 have a lower mass ratio of dissolved iron in the negative electrode, a higher cycle capacity retention rate and a lower cycle gas production growth rate than the materials prepared in each comparative example.

[0176] In addition, compared with Examples 1 to 7, the capacity retention rates of Examples 8 and 9 are relatively low, while the Fe mass ratio and gas production growth rate are higher. This may be due to the slow heating rate of the first sintering treatment during the preparation of the sample in Example 8, while the heating rate of the first sintering treatment during the preparation of the sample in Example 9 is fast.

[0177] 4. After the full battery made of the materials of each embodiment and comparative example used in Experimental Example 4 was cycled for 100 cycles in a 45°C environment, the charge and discharge curves were differentiated to obtain dQ / dV, and whether an irreversible phase change occurred in the range of 3.7-4V was observed. It was observed that no irreversible phase change occurred in the range of 3.7-4V in Embodiments 1 to 11, while irreversible phase change occurred in the range of 3.7-4V in Comparative Examples 1 to 5.

[0178] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A sodium positive electrode material, characterized in that: The molecular formula of the sodium positive electrode material is Na a Ni b Ti c Fe d Mn e X f O2, wherein: 0.94≤a≤1.04, 0.20≤b≤0.30, 0.001≤c≤0.1, 0.3≤d≤0.4, 0.3≤e≤0.5, 0.001≤f≤0.02, X element is selected from at least one of Cu and Ag; the X element accounts for 0.5wt%-2wt% of the surface mass of the sodium positive electrode material.

2. The sodium positive electrode material according to claim 1, characterized in that The initial discharge capacity of the sodium cathode material is greater than or equal to 130 mAh / g; and / or, The powder resistance under a pressure of 18 MPa is less than or equal to 320,000 Ω*cm; and / or, After the full battery including the positive electrode material is cycled 100 times in a 45°C environment, the capacity retention rate is greater than or equal to 94.5%, and the Fe element dissolution amount of the negative electrode is less than or equal to 50 ppm.

3. The sodium positive electrode material according to claim 1 or 2, characterized in that: The single particle compressive strength of the sodium positive electrode material is greater than or equal to 190 MPa; and / or, The Dv3 of the sodium positive electrode material is greater than 2 μm; In the dQ / dV spectrum of a full battery including the positive electrode material measured after 100 cycles in a 45°C environment, no irreversible phase change occurs in the 3.7-4V range; and / or, The average voltage of the button cell 2-4V including the positive electrode material is greater than or equal to 3.1V.

4. A method for preparing a sodium positive electrode material according to any one of claims 1 to 3, characterized in that: The steps include: 1) performing a first sintering treatment on a mixed system including a nickel iron manganese oxide precursor, a titanium source and a sodium source to obtain a first sintered product; 2) performing a second sintering treatment on the mixed system including the first sintered product and the X element metal source to obtain the sodium battery positive electrode material; The treatment temperature of the first sintering treatment is 850-1000°C, and the holding time is 8-14h; The second sintering treatment has a treatment temperature of 400-800°C and a holding time of 6-12h; The general formula of the nickel iron manganese oxide precursor is Ni b Fe d Mn e (OH)2, 0.20≤b≤0.30, 0.3≤d≤0.4, 0.3≤e≤0.

5.

5. The method according to claim 4, characterized in that The first sintering treatment includes first heating the temperature to 600-700°C at a heating rate of 4-8°C / min, then heating the temperature to 850-1000°C at a heating rate of 1-2°C / min, and keeping the temperature for 8-14h; and / or, The second sintering treatment includes heating the temperature to 400-800° C. at a heating rate of 1-5° C. / min and keeping the temperature for 6-12 hours.

6. The method according to claim 4 or 5, characterized in that: The X element includes copper element and silver element, and the molar ratio of copper element to silver element is 1:(0.6-1.5).

7. The method according to any one of claims 4 to 6, characterized in that: The method also includes cooling the product obtained by the first sintering process to room temperature at a rate of 2-5°C / min.

8. The method according to any one of claims 4 to 7, characterized in that: The X element metal source is selected from at least one of copper oxide and silver oxide.

9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the sodium positive electrode material according to any one of claims 1 to 3.

10. A battery, characterized in that: The battery comprises the sodium positive electrode material according to any one of claims 1 to 3; and / or, The battery comprises the positive electrode sheet according to claim 9.

Citation Information

Patent Citations

  • O3-type layered positive electrode material for sodium ion battery and method for improving purity of material through element doping

    CN112310390A

  • Sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN117423825A

  • Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery

    CN118507691A

  • High-voltage stable sodium electrooxide positive electrode material and preparation method thereof

    CN118645609A

  • Sodium-nickel-copper-iron-manganese layered oxide positive electrode material, preparation method thereof, positive plate and sodium ion battery

    CN118841562A